Porous Collagen Scaffold Reinforced with Surfaced Activated PLLA Nanoparticles - Cancan Xu; Wei Lu; Shaoquan Bian; Jie Liang; Yujiang Fan; Xingdong Zhang (The Scientific World Journal)
Porous collagen scaffold is integrated with surface activated PLLA nanoparticles fabricated by lyophilizing and crosslinking via EDC treatment. In order to prepare surface-modified PLLA nanoparticles, PLLA was firstly grafted with poly (acrylic acid) (PAA) through surface-initiated polymerization of acrylic acid. Nanoparticles of average diameter 316 nm and zeta potential −39.88 mV were obtained from the such-treated PLLA by dialysis method. Porous collagen scaffold were fabricated by mixing PLLA nanoparticles with collagen solution, freeze drying, and crosslinking with EDC. SEM observation revealed that nanoparticles were homogeneously dispersed in collagen matrix, forming interconnected porous structure with pore size ranging from 150 to 200 μm, irrespective of the amount of nanoparticles. The porosity of the scaffolds kept almost unchanged with the increment of the nanoparticles, whereas the mechanical property was obviously improved, and the degradation was effectively retarded. In vitro L929 mouse fibroblast cells seeding and culture studies revealed that cells infiltrated into the scaffolds and were distributed homogeneously. Compared with the pure collagen sponge, the number of cells in hybrid scaffolds greatly increased with the increment of incorporated nanoparticles. These results manifested that the surface-activated PLLA nanoparticles effectively reinforced the porous collagen scaffold and promoted the cells penetrating into the scaffold, and proliferation.